Photooxygenations and Self-Sensitizations of Naphthylamines: Efficient Access to Iminoquinones - Ying Wei; Lei Tang; Chunxiao Zhong; Xinmiao Xie; Pengju Sun; Chen Sun; He Zhang; Xiang-ping Zheng; Xiuli Wang; Ling-hai Xie (Journal of Chemistry)
A series of spiro [fluorene-9,7′-dibenzo[c,h]acridine]-5′-one (SFDBAO) derivatives have been concisely and cleanly obtained by exposure to sunlight without external photosensitizers in the higher yields than that when using a UV lamp. An interesting autocatalyst and self-sensitive procedure have been proposed to explain the effective photooxygenation. SFDBAO derivatives exhibit the continuous π-stacks in single-crystal and electron-withdraw properties with red light-emitting and photovoltaic properties.